Supply Chain Management as a Driving Force for Generating Competitive Advantage for Dairy Companies - Irina Olegovna Poleshkina (Economic and Social Changes: Facts, Trends, Forecast, 2016)
The study aims to uncover the reserves to generate competitive advantages for the participants of the market of perishables in the case of the dairy sector due to the formation of effective supply chains, as this category of goods is the most demanding in terms of periods and conditions of transportation and terms of preservation. The research technique is based on the concepts of value chains and supply chain management. In order to optimize the distribution of functions between the participants of the dairy chain a process-based approach has been applied. The research has revealed the main reasons for high aggregate costs and the places of their formation at each stage of the dairy supply chain. The article proposes the mechanisms to address three main problems arising from the process of building relations between the participants of the dairy supply chain in Russia. These problems are associated with a disproportionate margin distribution between the participants of the chain, with non-compliance of the quality of raw milk with the requirements for the production of specific types of dairy products, and with distrust of the supply chain participants, which increases transaction costs and forces to create reserve supplies which reduce the competitiveness of the whole dairy supply chain in general. In order to improve the competitiveness of all participants in the dairy chain, the article presents several mechanisms for solving these problems. The first is margin distribution based on the costs incurred by each participant of the dairy chain. The second is the use of a mathematical model to determine the assortment of goods of a dairy enterprise on the basis of the incoming volume and quality of raw milk according to the seasonal factor and the demand for dairy products. The third is the feasibility of refusal from the formation of reserve supplies by all participants of the dairy chain, which will not only minimize aggregate costs, but also significantly improve the quality of dairy products actually available to consumers in retail trade